Implementation of the Preparation and Presentation of Financial Statements Based on SAK EMKM - Risawatie, Risawatie; Azizah, Nurul (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Law No. 20 of 2008 concerning Micro, Small and Medium Enterprises can be used as a reference in defining and providing a quantitative range of EMKM. Is a financial standard set to facilitate MSMEs in compiling and presenting more informative financial reports with the aim of providing convenience for investors and creditors in providing financing assistance for MSME entrepreneurs. This research is designed to produce a financial report format for SMEs based on SAK EMKM. The object of this research is MSMEs in Mojokerto, which are engaged in the delivery of goods, food and beverages. This research is qualitative research. Collecting data in this study through field studies, observations, interviews and literature studies. The results of research that have been carried out conclude that 1) there are MSMEs that have not implemented SAK EMKM. The financial recording system is done manually is very simple. 2) the factors that caused the failure of SAK EMKM in MSMEs were due to internal factors in the form of a lack of understanding of abilities in the accounting field, while external factors were due to the lack of participation from the Ministry of Cooperatives and MSMEs and the Cooperative Service. The purpose of this study is to directly conduct training to MSME business actors so that they can understand and implement SAK EMKM for the business they run.